A multi-centre study comparing granulocyte-colony stimulating factors to antibiotics for primary prophylaxis of docetaxel-cyclophosphamide induced febrile neutropenia. (August 2021) - Clemons, Mark; Fergusson, Dean; Joy, Anil A.; Thavorn, Kednapa; Meza-Junco, Judith; Hiller, Julie Price; Mackey, John; Ng, Terry; Zhu, Xiaofu; Ibrahim, Mohammed F.K.; Sienkiewicz, Marta; Saunders, Deanna; et al.
Abstract: Background: Primary febrile neutropenia (FN) prophylaxis with ciprofloxacin or granulocyte-colony stimulating factors (G-CSF) is recommended with docetaxel-cyclophosphamide (TC) chemotherapy for early-stage breast cancer (EBC). A pragmatic randomised trial compared the superiority of G-CSF to ciprofloxacin and a cost-utility analysis were conducted. Methods: EBC patients receiving TC chemotherapy were randomised to ciprofloxacin or G-CSF. The primary outcome was a composite of FN and non-FN treatment-related hospitalisation. Secondary outcomes included; rates of FN, non-FN treatment-related hospitalisation, chemotherapy dose reductions/delays/discontinuations. Primary analysis was performed with the intention to treat population. Cost-utility analyses were conducted from the Canadian public payer perspective. Results: 458 eligible patients were randomised: 228 to ciprofloxacin and 230 to G-CSF. For the primary endpoint there was non-statistically significant difference (Risk difference = −6.7%, 95%CI = −13.5%–0.1%, p = 0.061) between ciprofloxacin patients (46, 20.2%) and G-CSF (31, 13.5%). Patients receiving ciprofloxacin were more likely to experience FN (36/228, 15.8% vs 13/230, 5.7%) than patients receiving G-CSF (p < 0.001). Non-FN treatment-related hospitalisation occurred in 40/228 (17.5%) of ciprofloxacin patients vs 28/230 (12.2%) of G-CSF patients (p = 0.12). There were no differences in other secondary outcomes. G-CSF was associated with an incremental cost-effectiveness ratio of C1, 760, 796 per one quality-adjusted life year gained. Conclusion: The primary endpoint of superiority of G-CSF over ciprofloxacin was not demonstrated. While there were reduced FN rates with G-CSF, there were no differences in chemotherapy dose delays/reductions or discontinuations. With the commonly used willingness to pay value of C50, 000/QALY, G-CSF use was not cost-effective compared to ciprofloxacin and deserves scrutiny from the payer perspective. Highlights: Primary febrile neutropenia (FN) prophylaxis is indicated for docetaxel-cyclophosphamide (TC) chemotherapy. In this multicentre trial 458 breast cancer patients receiving TC chemotherapy were randomised to ciprofloxacin or to G-CSF. For the primary endpoint of FN and non-FN treatment-related hospitalizations, G-CSF was not superior over ciprofloxacin. While there were reduced FN rates with G-CSF, the incremental cost-effectiveness ratio was C1, 760, 796 per one QALYWALY gained.